Improving the effectiveness of risk management among sub-contractors in the northern state of Malaysia / Nurqameela Md Radzi, Kartina Alauddin and Mohmad Mohd Derus - Md Radzi, Nurqameela; Alauddin, Kartina; Mohd Derus, Mohmad (UiTM Press, 2022)
The risk should be managed crucially by any level of multidiscipline. Construction activities involved hazardous situations and unpredictable incidents during construction. There is a central issue triggered by sub-contractors' tasks, i.e., failure to manage the risk management of main contractors effectively. Many factors contributed to the ineffectiveness of risk management implementation among sub-contractors, including lack of skills and expertise, lack of experience, and communication breakdown with the team. Therefore, this paper significantly provides the results of a survey of sub-contractors involved in the Northern construction projects. The goal of this study concerns the strategies to improve the effectiveness of sub-contractors in managing the risk on site. These are described with the results of the questionnaire survey analysis from 300 respondents. The respondents are from sub-contractors among G1 to G4 in the northern state of East Malaysia. Using the Kruskal-Wallis test, sixteen strategies were identified from the literature have been tested among the sub-contractors. The finding reveals that only ten approaches, i.e., effective site management and supervision, experience contractors, good feasibility studies, project understanding, thoroughly investigate vendor capabilities, frequent progress meetings, systematic coordination between parties, allocation enough resources, the right path, and proper identification of risk does give significant strategies to improve implementation of risk management among sub-contractors in the northern states of Malaysia.